Ações colaborativas para encaminhamentos da produção e da reescrita textual no ensino fundamental - Schoffen, Rosemary de Oliveira (2016)
Since the 1980s, the Portuguese Language teaching has been discussed by scholars and researchers, based on language s supposed dialogue and interaction, as defended by the Bahktin Circle, which is the theory found in the official Curricular Guidelines (DCE) of Parana State (Brazil), which recognize the mentioned text as a teaching unit that happens in a certain discursive genre. Thus, the proposals of text productions in school should prioritize interaction, considering that for Bakhtin/Volochinov (2014[1929]), language is materialized only in concrete enunciates within a process of dialogue. The distance of such premises comprehension by Portuguese Language teachers leads to the inference that such premises were not fully understood, perhaps by the absence of adequate training and/or a period of time sufficient to articulate theory and practice, according to the document s requirements. Being part of this school reality, teaching classes in public schools, we have chosen to develop a critical-collaborative-action-research involving two 6th to 9th graders teachers of middle school, in a Northwestern city in Parana State. Therefore, the focus was specifically to the following theme: collaborative actions in the teaching practice concerning to the production and texts rewriting. Such option is justified by an understanding that continued training, based in principles of collaborative actions can help with theory-methodology premises of writing and rewriting texts, which guarantees a safer pedagogical practice development. Such investigation purpose is sustained by the following questions: a) How do 6th to 9th graders teachers understand the theory and methodology premises present in the DCE? b) What have 6th to 9th graders teachers been doing regarding to the orientation for writing and rewriting texts? c) how can we researchers develop collaborative actions focused on teachers difficulties related to their orientation for writing and rewriting texts, as to consider the theory and methodology orientations present in the DCE? d) What changes in theory and methodology are introduced based on the researcher s mediation actions? In such a way, this paper s main purpose was to think about the collaborative actions developed in the theory and methodology orientations regarding the practice of production and text rewriting and their contributions to the theory and methodology orientations in the final grades of middle school. This research is has its foundations in Applied Linguistics, under the conception of language as presented by the Bakhtin Circle, supported by the principles of historical and cultural theory, from the studies of Vygotsky, Luria, and Leontiev, and from the text writing premises proposed first by Geraldi (2007[1984]), passing by some other researchers in this field. We assume, as a methodology proceeding, the methodology principle of critical-collaborative-action research, as we promote reflections with middle school teachers on their own practice, in order to build new knowledge about the methodology orientations on production and rewriting of a text. The results of the whole research process show: a) the understanding of the process of text writing which comprehends the steps of planning, actual writing, revising, and rewriting; b) the improvement of activities of development for writing and 9 rewriting texts; c) the internalization and appropriation of the theoretical and methodological premises concerning the concept of language as interaction and dialogue; d) the need to review the way how to continue to offer teacher´s training in the middle school context; e) the need to invest in collaborative theory and methodology orientations regarding the work with writing, which enables the follow-up of the pedagogical practice in this teaching context.